Novel Developments in Stem Cell Mobilization Focus on CXCR4 - Fruehauf, Stefan.; Fruehauf, Stefan.; Zeller, W. Jens.; Zeller, W. Jens.; Calandra, Gary.; Calandra, Gary. (Springer New York : Imprint: Springer, 2012)
Recently, the CXCR4/CXCL12-axis has been recognized as one of the pivotal adhesion pathways by which hematopoietic stem cells are retained in the bone marrow. CXCR4 antagonists with different chemical specification are being developed. Pharmacology research guides the way to the rational development of effective antagonists. One antagonist, plerixafor, is now clinically approved for stem cell mobilization of lymphoma and myeloma patients. This progress allows patients to receive potentially life-saving treatment which could not have been administered otherwise. Through early clinical studies it was recognized that CXCR4 antagonists also mobilize malignant hematopoietic cells, i.e. leukemia cells. In preclinical studies, a sensitization of mobilized leukemic cells to standard cytotoxic chemotherapy could be shown. CXCR4 antagonists are an exciting new class of compounds which are also used for the mobilization of angiogenic cells or for the treatment of solid tumors. This book provides concise reviews of novel developments, as well as possible future developments on CXCR4.  .